"Some of us actually choose to do this": The meanings of sex work from the perspective of female sex workers in Denmark. Issue 1 (2nd January 2022) - Huglstad, Mille; Halvorsen, Ingrid Louise Isabell; Jonsson, Hans; Nielsen, Kristina Tomra
ABSTRACT: Introduction: The aim of this study was to investigate how female sex workers perceive and describe meaning when engaging in the non-sanctioned occupation of sex work. Method: In-depth semi-structured interviews were carried out with six sex workers aged 26 to 56 years who were working either part-time or full-time at a brothel or worked "privately & discreetly." Interpretative phenomenological analysis was applied to develop themes representing the subjective perspectives of the participants. Findings: Mostly, the participants perceived and described their engagement in sex work as holding positive meanings and contributing to their well-being and quality of life. Participants perceived and described the society's view on sex work as the most challenging part of their engagement in sex work. Six themes emerged from the data: 1) sexual beings, 2) personal development, 3) interpersonal relationships, 4) proud professionals, 5) the public view on sex work and 6) well-being and quality of life. Conclusion: Engagement in sex work was found to be meaningful to the participants as their doing was intrinsically motivated by their being, making them become more knowledgeable, skilled, confident, and empowered and contributed to a sense of belonging. Engagement in sex work was also found to hold negative meaning, as a limited sense of belonging to society was described. Despite this negative aspect, engagement in sex work was deemed to be meaningful and engaging and contributed to their well-being and quality of life. Further research is required to develop knowledge about other sex workers.